2018
DOI: 10.5664/jcsm.6938
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome in Iranian People With Type 2 Diabetes Mellitus: The Role in Quality of Life and Quality of Sleep

Abstract: RLS has an independent and significant role in sleep quality and QoL in the patients with diabetes. Neuropathy with RLS does not confer any additive burden on QoL and sleep quality of this population of patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…In this study, diabetic patients reported high prevalence of RLS (22.8%), and this is confirmative with other studies conducted in Iran (19.5%),[8] Bosnia and Herzegovina (21%),[13] the United States (24.5%),[5] Brazil (27%),[11] and Turkey (28.3%). [6] This result supports the study findings of other studies[1314161718] that sleep disorders correlate highly with hypertension and diabetic population in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, diabetic patients reported high prevalence of RLS (22.8%), and this is confirmative with other studies conducted in Iran (19.5%),[8] Bosnia and Herzegovina (21%),[13] the United States (24.5%),[5] Brazil (27%),[11] and Turkey (28.3%). [6] This result supports the study findings of other studies[1314161718] that sleep disorders correlate highly with hypertension and diabetic population in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…[456] RLS can have profound negative effects on the quality of life and daily activities and is associated with significant economic, social, and healthcare burdens. [78910] RLS has been significantly associated with diabetes, hypertension, obesity, and metabolic syndrome;[56] meanwhile, the situation and role of these relationships remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, restless leg syndrome was found in 31.7% of patients compared to 10.3% of control subjects, the present finding was higher than the result of (Harashima et al [20] (8%), The current findings were similar to a study published by Zobeiri et al [21] who concluded a prevalence of 28.6% compared to 7.1% in control subjects. Previous studies from other countries found lower rates of RLS among patients with diabetes [22,23]. A previous study [24] showed no association of the restless leg syndrome with type 2 diabetes in contradiction to the current findings.…”
Section: The Relationship Of the Restless Syndrome (No=26) To Sex Necontrasting
confidence: 99%
“…The current findings were similar to a study published by Zobeiri et al who concluded a prevalence of 28.6% as compared to 7.1% in control subjects [21]. Previous studies from other countries found lower rates of RLS among patients with diabetes [22][23]. A previous study showed no association of restless legs syndrome with type 2 diabetes in contradiction to the current findings [24].…”
Section: Discussionsupporting
confidence: 87%